Adult Survival in Ellis-van Creveld Syndrome with Common Atrium – A Rare Case Report - Mugula Sudhakar Rao (Journal of Clinical and Diagnostic Research, 2017)
Ellis-van Creveld syndrome is a rare genetic disorder, characterized by chondral dysplasia, ectodermal dysplasia, polydactyly and congenital heart defects. Patients with this syndrome rarely survive into adulthood. The syndrome has also been rarely reported in the Indian population. We present the case of a 56 year old female who presented with post-menopausal bleeding, and was diagnosed with Ellis van Creveld syndrome, with a common atrium and common atrioventricular valve.